Khrōngkān sưksā ph̄ưa čhattham ph̄æn patibat kānphatthanā kānth̨ōngthīeo Čhangwat Krabī, Trang, Satun, læ Phatthalung : rāingān chabap sombūn (final report) (Kānth̨ōngthīeo h̄æng Prathēt Thai, 2002)
Action plan for tourism development in Krabi, Trang, Satun and Pattalung, provinces in Southern Thailand.